Electrospray Encapsulation of Antithrombotic Drug into Poly (L-lactic acid) Nanoparticles for Cardiovascular Applications. (2019) - Bakola, V.; Tsiapla, A.R.; Karagkiozaki, V.; Pappa, F.; Pavlidou, E.; Moutsios, I.; Gravalidis, C.; Logothetidis, S.
Abstract: Nowadays, the most common revascularization procedure to combat coronary artery disease is through Percutaneous Coronary Intervention (PCI) with the use of arterial stents. Two of the most recurrent drawbacks of stenting are restenosis and late stent thrombosis. To render the stent effective, a long-term antiplatelet drug delivery system have to be incorporated into a biodegradable polymer to target directly the malevolent site. A novel drug delivery nanosystem of Poly(D, L-lactic acid) (PLA) nanoparticles (NPs) loaded with Dipyridamole (DPM) was fabricated via electrospraying that forms monodispersed, biodegradable drug loaded NPs, as coating for cardiovascular stents. This study presents a feasible degradable NP delivery system that encapsulates, protects and controls the release of DPM, intended to reduce the possibility of thrombosis inside the stent.